2022
DOI: 10.1186/s13011-022-00484-0
|View full text |Cite
|
Sign up to set email alerts
|

Intention to seek emergency medical services during community overdose events in British Columbia, Canada: a cross-sectional survey

Abstract: Introduction Canada and the United States continue to experience increasing overdose deaths attributed to highly toxic illicit substances, driven by fentanyl and its analogues. Many bystanders report being hesitant to call 9-1-1 at an overdose due to fears around police presence and arrests. In Canada, a federal law was enacted in 2017, the Good Samaritan Drug Overdose Act (GSDOA), to provide protection from simple drug possession and related charges when 9-1-1 is called to an overdose. There i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Studies have shown that awareness and correct knowledge of locally applicable Good Samaritan Laws remains low among people who use drugs and potential bystanders [ 15 18 ]. Better knowledge of Good Samaritan Laws has generally been associated with an increased frequency of bystanders calling 911 and otherwise seeking medical help when witnessing an overdose [ 16 , 19 21 ].However, even when knowledge about the laws is correct, distrust of law enforcement and fear of legal consequences may stand in the way of bystanders seeking help [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that awareness and correct knowledge of locally applicable Good Samaritan Laws remains low among people who use drugs and potential bystanders [ 15 18 ]. Better knowledge of Good Samaritan Laws has generally been associated with an increased frequency of bystanders calling 911 and otherwise seeking medical help when witnessing an overdose [ 16 , 19 21 ].However, even when knowledge about the laws is correct, distrust of law enforcement and fear of legal consequences may stand in the way of bystanders seeking help [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%